Li‐Fraumeni and Li‐Fraumeni—like syndrome among children diagnosed with pediatric cancer in Southern Brazil. Issue 24 (7th October 2013) - Giacomazzi, Juliana; Selistre, Simone G.; Rossi, Cristina; Alemar, Barbara; Santos‐Silva, Patricia; Pereira, Fernando S.; Netto, Cristina B.; Cossio, Silvia L.; Roth, Daniela E.; Brunetto, Algemir L.; Zagonel‐Oliveira, Marcelo; Martel‐Planche, Ghyslaine; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Pediatric cancers are a feature in patients with Li‐Fraumeni syndrome and its variant Li‐Fraumeni–like syndrome (LFS/LFL). To the best of the authors' knowledge, TP53 germline mutations are currently the only molecular defect known to be associated with this disease. Recently, a specific germline mutation in this gene, p.R337H, has been reported at a high prevalence in Brazil. METHODS The prevalence of LFS/LFL was investigated in children with cancer who were diagnosed with tumors on the LFS/LFL spectrum and in a small consecutive series of controls without cancer. The prevalence of the germline p.R337H mutation and of other germline TP53 mutations was investigated in a general group of children with cancer and exclusively in children fulfilling the clinical criteria for LFS/LFL, respectively. RESULTS Among the 65 children without cancer, 1.5% had a family history of LFL whereas of the 292 children with cancer, 25.3% had a family history of LFL (P < .001). Screening for the p.R337H mutation identified 11 carriers (3.7%), 9 of whom were diagnosed with adrenocortical carcinomas (ACC) and 2 of whom were diagnosed with choroid plexus carcinomas. One of the ACC probands was homozygous mutant. The Brazilian founder haplotype and loss of heterozygosity at the p.R337H locus were present in all carriers. In addition, direct sequencing of the entire TP53 coding region and gene rearrangement analysis of probands fulfilling the criteria for LFL (Eeles 2 criteria, Birch and/or Chompret criteria) and who were negative for the p.R337H mutation revealed a DNA‐binding domain pathogenic mutation, p.G245S, in 1 child. CONCLUSIONS TP53 p.R337H testing should be offered to Brazilian children diagnosed with ACC and choroid plexus carcinoma. A significant percentage of children with cancer in southern Brazil fulfill the criteria for LFL and should be referred for genetic risk assessment. Cancer 2013;119:4341–4349. © 2013 American Cancer Society.